Disorders of Sex Development in Individuals Harbouring MAMLD1 Variants: WES and Interactome Evidence of Oligogenic Inheritance - Li, Lele; Gao, Fenqi; Fan, Lijun; Su, Chang; Liang, Xuejun; Gong, ChunXiu (Frontiers in Endocrinology, 2020)
Background. MAMLD1 (mastermind-like domain-containing 1) plays an important role in modulating testosterone production during sex development and is involved in 46,XY disorders of sex development (DSDs).Recently, there has been controversy regarding the causative role of MAMLD1 variations in DSDs. Methods. We described a clinical series in 46, XY DSD children with MAMLD1 variants from unrelated families, examined the hypothesis of a possible oligogenic mode of inheritance, and performed whole exome sequencing (WES). WES data were filtered by common tools and a disease-tailored algorithm including MAMLD1-related and DSD-related known and candidate genes. Results. The salient phenotype was hypospadias (8/10); other phenotypes included cryptorchidism, bifid scrotum, and/or micropenis. Nine sequence variants were identified, including six missense (p.P334S, p.S662R, p.A421P, p.T992I, p.P542S, and p.R927L) and three nonsense variations (p.R356X, p.Q152X, and p.Q124X). Six variants were reported for the first time (p.Q152X, p.Q124X, p.P334S, p.S662R, p.A421P, and p.R927L). Forty-three potentially deleterious/candidate variants in 18 genes (RET, CDH23, MYO7A, NOTCH2, MAML1, MAML2, CYP1A1, WNT9B, GLI2, GLI3, MAML3, WNT9A, FRAS1, PIK3R3, FREM2, PTPN11, EVC, FLNA) were identified, which may contribute to each patient’s phenotype. MYO7A were the most commonly identified genes. Combination variants of genes were also identified. Interactome analysis showed that MAMLD1 connects directly to MAML1/2/3and NOTCH1/2. ThroughNOTCH1/2, 8 genes are associated with MAMLD1—WNT9A/9B, GLI2/3, RET, FLNA, PTPN11, and EYA1. Conclusions. Our findings provided further evidence that the broad phenotypic spectrum of MAMLD1-related 46,XY DSD subjects may at least partially be caused by oligogenic inheritance.